Awangs boys storm into quarters - Xavier, Francis (New Sabah Times English (KK), 2012)
KOTA KINABALU: Sabah Under-19 coach Awang Sabtu Jamil is taking one match at time as he quietly sets his sights in guiding his charges into the championship decider.